HnRNPL inhibits the osteogenic differentiation of PDLCs stimulated by SrCl(2) through repressing Setd2 - Jia, Xiaoshi (J Cell Mol Med, 2019)
Osteoporosis has been shown to intensify bone loss caused by periodontitis and both share common risk factors. One strategy utilized to manage the disease has been via the release of Sr ions by Strontium Ranelate having a direct effect on preventing osteoclast activation and promoting osteoblast differentiation. Previously we have developed and characterized porous Sr‐mesoporous bioactive glass (Sr‐MBG) scaffolds and demonstrated their ability to promote periodontal regeneration when compared to MBG alone. Our group further discovered a splicing factor, heterogeneous nuclear ribonucleoprotein L (hnRNPL), was drastically down‐regulated in periodontal ligament stem cells (PDLCs) stimulated by Sr through the activation of AKT pathway. Furthermore, hnRNPL restrained the osteogenic differentiation of PDLCs through down‐regulating H3K36me3‐specific methyltransferase Setd2. The goal of the present study was to investigate the mechanism of periodontal regeneration stimulated by Sr It was first found that the epigenetic mechanism of splicing factor hnRNPL participated in the osteogenesis processing of PDLCs stimulated by SrCl(2). Meanwhile, the different role of hnRNPL and SET domain containing 2 (Setd2) may provide some implication of the treatment of periodontitis patients simultaneously suffering from osteoporosis.